2017
DOI: 10.1146/annurev-clinpsy-021815-093253
|View full text |Cite
|
Sign up to set email alerts
|

Trait Impulsivity and the Externalizing Spectrum

Abstract: This article reviews evidence that trait impulsivity-expressed early in life as the hyperactive-impulsive and combined presentations of attention-deficit/hyperactivity disorder (ADHD)-is a bottom-up, subcortically mediated vulnerability to all externalizing disorders. This vulnerability arises from deficient mesolimbic dopamine responding, which imbues psychological states (irritability, discontentment) that motivate excessive approach behavior (hyperactivity, impulsivity). Through complex interactions with (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
186
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 167 publications
(198 citation statements)
references
References 148 publications
(187 reference statements)
11
186
0
1
Order By: Relevance
“…These genetic factors have been linked multiple structural (e.g., smaller volume) and functional (e.g., underactivation, impaired connectivity) brain abnormalities in individuals with ADHD which compromise the functioning of neural circuits related to attention, inhibitory control, reward motivation, and emotional regulation and which in turn can be linked to ADHD symptoms and consequent impairments in major life activities [3,7,9,15,16,17]. However, although the evidence for these linkages is robust, the research is correlational and therefore cannot be interpreted as causal on the sole basis of the linkage [16].…”
Section: Abnormal Brain Functioningmentioning
confidence: 99%
See 4 more Smart Citations
“…These genetic factors have been linked multiple structural (e.g., smaller volume) and functional (e.g., underactivation, impaired connectivity) brain abnormalities in individuals with ADHD which compromise the functioning of neural circuits related to attention, inhibitory control, reward motivation, and emotional regulation and which in turn can be linked to ADHD symptoms and consequent impairments in major life activities [3,7,9,15,16,17]. However, although the evidence for these linkages is robust, the research is correlational and therefore cannot be interpreted as causal on the sole basis of the linkage [16].…”
Section: Abnormal Brain Functioningmentioning
confidence: 99%
“…Among the various disorders, the strongest link is with sequential development of disorders in the externalizing spectrum, i.e., Oppositional Defiant Disorder, Conduct Disorder, Substance Use Disorder, and Antisocial Personality Disorder [8,15,22]. This developmental cascade in turn increases the risk for juvenile delinquency and adult criminality such that a systematic review and meta-analysis of 11 prospective studies (N=15,442) found that childhood ADHD was significantly associated with increased risk for juvenile arrests (RR: 2.2, 95%, CI: 1.3-3.5),convictions (RR: 3.3, 95%, CI: 2.1-5.2), and incarcerations (RR: 2.9, 95%, CI: 1.9-4.3) [23].…”
Section: Mental Health Impairmentsmentioning
confidence: 99%
See 3 more Smart Citations